Tubular glomerulus unbalance in children and adolescents with a history of low birth weight - Iecienia Espinosa Santisteban; Luis Borges Mesa; Aydelin Pérez Ramos; María Ofelia Barber Fox; Adina Pérez Mejías (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: The tubular glomerulus unbalance with tubular preponderance may contribute to the hypertension onset. This hypertensor mechanism is proposed starting from obtaining a hypertension experimental model, achieves with the administration of inhibitors of the renin-angiotensin system. It has not been studied if this same mechanism contributes to the development of hypertension that appears in individual's adulthood with anamnesis of low birth weight due to an intrauterine growth retardation. Objective: To evaluate the existence of tubular glomerulus unbalance with tubular preponderance in normotensive individuals with a medical record of low birth weight due to an intrauterine growth retardation. Material and Methods: 78 normotensive children and teenagers were studied. Of these, 19 were between 4 and 5 years (N-IUGR) and 20 from 14 to 15 years (A-IUGR) with a medical history of intrauterine growth retardation, the rest constituted the respective control groups. Mean arterial tension, glomerular filtration intensity and sodium proximal tubular reabsorption was determined. Results: Increase of mean arterial tension values in teenagers with medical records of Retarded Intrauterine Growth (A-CIUR x = 86.3 ± 8.6 vs. A-Control x = 80.9 ± 4.7) were found. Glomerular Filtration Intensity and endogenous lithium clearance showed no differences. Na / Li countertransporter activity of erythrocyte decreased in both groups (N-CIUR x = 4.8 * ± 2.4 vs N-Control x = 7.9 ± 4.0) and (A-CIUR x = 1.9 * * ± 0.7 vs A-Control x = 9.6 ± 1.1). Conclusions: There is insufficient evidence to deny or confirm the existence of tubular glomerulus unbalance with a tubular glomerulus predominance in the studied individuals. Keywords: essential arterial hypertension, retarded intrauterine growth, tubular glomerulus unbalance, children, teenagers, glomerular filtration intensity, Sodium-lithium countertransporter activity.